Thermodynamic Laws and Measurements - Hathaway, George (Journal of Scientific Exploration, 2022)
This paper outlines issues associated with the verification of claims of thermodynamic law violations, focusing on measurement issues. We do not go into detail about the various interpretations and alternative forms of the thermodynamic “laws”, only presenting the reader with a standard interpretation of Laws 1 & 2. The word “laws” is in quotes here as there have been recent experiments appearing to show violations of, or at least subtleties associated with these laws which necessitate proper measurements and experimental design.